2024
DOI: 10.1055/a-2269-1123
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Bleeding Risk: An Ecological Epidemiological Study Comparing Korea and United Kingdom Subjects

Dong-Seon Kang,
Pil-Sung Yang,
Daehoon Kim
et al.

Abstract: Background: This study aimed to evaluate racial differences in bleeding incidence by conducting an ecological epidemiological study using data from Korea and the UK. Methods: We included healthy participants from the Korean National Health Insurance Service-Health Screening and the UK Biobank who underwent health examinations between 2006 and 2010 and had no comorbidities or history of medication use. Finally, 112,750 East Asians (50.7% men, mean age 52.6 years) and 210,995 Caucasians (44.7% men, mean age 55.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…CT data included patients from over 100 countries, whereas RWD are only from the US. Previous studies have shown ethnic and racial differences in bleeding complications associated with DOACs [38,39], and hence, the population/ethnic differences could have impacted the results seen in our study, given ethic differences in stroke and bleeing rates [40][41][42].…”
Section: Limitationsmentioning
confidence: 78%
“…CT data included patients from over 100 countries, whereas RWD are only from the US. Previous studies have shown ethnic and racial differences in bleeding complications associated with DOACs [38,39], and hence, the population/ethnic differences could have impacted the results seen in our study, given ethic differences in stroke and bleeing rates [40][41][42].…”
Section: Limitationsmentioning
confidence: 78%
“…12 Some evidence suggests that Asian patients are more sensitive to anticoagulation, in terms of bleeding, 13,14 but ethnic differences in thromboembolism and intracranial bleeding are evident. 15,16…”
Section: Epidemiology Of the Elderly Af Populationmentioning
confidence: 99%
“…The impact of associated metabolic comorbidities and their changes over time (risk being dynamic rather than a static measure) also require consideration. Given the racial and sex differences in thrombotic (and bleeding) outcomes, 17,18 the picture is very likely to be far more complex.…”
mentioning
confidence: 99%